HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TIKTOK DAN PEMAHAMAN MENGENAI BULLYING PADA SISWA KELAS V SD NEGERI DI KELURAHAN CENGKARENG TIMUR - Zettriz Yuliana; Otib Satibi Hidayat; Imaningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the relationship between the intensity of TikTok usage and the understanding of bullying among fifth-grade students at public elementary schools in Cengkareng Timur, West Jakarta. The research employed a quantitative correlational method, using closed-ended Likert-scale questionnaires as the data collection instrument. A total of 91 students were selected through simple random sampling from two schools. Data analysis revealed a significant positive relationship between TikTok usage intensity and bullying comprehension, with a Pearson correlation coefficient of 0.675 and a significance value of 0.000 (< 0.05). The coefficient of determination showed that 45.6% of students’ understanding of bullying was influenced by their intensity of TikTok usage, while the remaining 54.4% was affected by other factors. These findings support Bandura’s social learning theory, suggesting that exposure to social media content contributes to students’ knowledge and attitudes toward bullying.